Transcatheter Aortic Valve Implantation: A Report on Serbia's First Systematic Program - Boljevic, Darko; Bojic, Milovan; Farkic, Mihajlo; Sagic, Dragan; Topic, Dragan; Kovacevic, Vladimir; Lakcevic, Jovana; Veljkovic, Stefan; Dobric, Milan; Hinic, Sasa; Ilijevski, Nenad; Nikolic, Marko; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Severe aortic stenosis, a highly-common valve disease in the elderly, has a poor prognosis if left untreated. To address the concern of effective procedures for severe aortic stenosis, a systematic TAVI program was established at the Dedinje Cardiovascular Institute (Belgrade, Serbia). Methods Our cohort was composed of 56 patients (74±15 years old). The mean logistic EuroScore was 10.17%; the mean Society of Thoracic Surgeons score was 3.22%. One third of the patients were categorized as class III or IV of the New York Heart Association (NYHA). The valves selected for use were either self-expandable or balloon expandable (Evolut R, Medtronic; Acurate Neo, Boston Scientific and Myval, Meril). The choice of valve type was made by the Institute's Structural Heart Team, in accordance with the patient's native aortic valve, size and calcification of ilio-femoral vessels, as well as the need for alternative access. TAVI procedure was conducted according to current guidelines provided by the European Society of Cardiology. Results The procedure success rate was 100%. Trans-femoral approach was achieved in 100% of patients; percutaneously in 87.5%, while a surgical cut was necessary in 12.5%. No patient showed moderate or severe aortic regurgitation after the procedure, although trace or mild regurgitation was recorded in 30.3%. Permanent pacemaker was implanted in one patient (1.78%), contrast induced acute kidney injury occured in one patient (1.78%), no stroke was recorded, and three pseudo-aneurysms which required surgical intervention occurred. Three patients required blood transfusions (5.33%). A 30-day all-cause mortality rate was 1.78%. Conclusion The Dedinje Cardiovascular Institute spearheaded all efforts to establish a TAVI program in Serbia. Our initial TAVI results are promising, encouraging, and comparable with the results of previous large randomized trials. This initial experience opens the door for further development with a goal of our Institute to become a high-volume TAVI center.